PENGARUH ULASAN PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA MARKETPLACE SHOPEE DI KABUPATEN SRAGEN - Latifah, Eva; Widiastuti, Erni (Surakarta Management Journal, 2023)
This research aims to determine the influence of product reviews, price, and promotions on purchasing decisions for Shopee marketplace users in Sragen Regency either partially and simultaneously. This research is a quantitative researcah. The population of this research are Shopee marketplace users in Sragen Regency. While the samples taken were 100 respondents with the sampling technique used was purposive sampling. The analysis techniques used is multiple linear regression analysis, t test, F test, and determination coefficient (R2). The results of the research show that partially, product review variable had a positive and significant effect on purchasing decisions. Price variable has a negative and significant effect on purchasing decisions. Promotion variable has a positive and significant effect on purchasing decisions. Simultaneously, product review, price, and promotion variables influence purchasing decisions.